The influence of pronunciation instruction on the perception and production of english word-final consonants - Silveira, Rosane (2004)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.